Bridging the gap between theory, research, and practice the role of child development laboratory programs in early childhood education - McBride, Brent A.; Barbour, Nancy E. (Elsevier/JAI, 2003)
University-based child development laboratory programs have a long and rich history. Since their inception in the mid-1920's they have played a vital role in adding to our expanding knowledge base on child development and early childhood education. In addition to their instrumental functions in the generation of new knowledge, these programs have played significant roles in the professional development of future early childhood educators. Through a variety of mechanisms these programs provide students with opportunities to begin applying the theory and knowledge being presented in college courses to actual practice in working with programs serving young children and their families. In recent years campuses have reconsidered, reconceptualized, and restructured the ways in which these laboratory programs fit within the agendas and missions of the universities where they are located, the local communities surrounding the universities, and the child development and early childhood education professions in general. The purpose of this volume is to present papers that identify emerging issues and challenges facing child development laboratory programs nationwide as they seek to solidify the roles they play within the child development and early childhood education fields. A goal of the volume is to present a collection of papers that can facilitate a dialogue among professionals on the ways in which child development laboratory programs can continue their important contributions toward the generation of new knowledge in child development and early childhood education, as well as support the professional development of students preparing for careers in these fields.
Keywords: Laboratory schools -- United States.; Early childhood education -- Research -- United States.; Child development -- Research -- United States.; Organization & management of education.; Pre-school & kindergarten.; Education -- Research.; elektronické knihy; electronic books